School Strategy Management in Optimizing Inclusive Education in Public Schools (Descriptive Study at SMKN 1 Palasah and SMPN 2 Dawuan) - Eri Arif Munandar; Lilis Suwandari (Universitas Negeri Malang, 2025)
Abstract: This study discusses school strategic management in optimizing inclusive education in public schools, with case studies at SMKN 1 Palasah and SMPN 2 Dawuan, Majalengka Regency. The background of this research is the need for appropriate strategies so that students with special needs receive fair and suitable educational services. The purpose of this study is to identify how schools plan, implement, and evaluate inclusive strategies, and to compare their impact on school culture. This research applied a qualitative descriptive method with data collected through interviews, observations, and documentation. The findings show that both schools are committed to inclusive education, but differ in readiness and implementation. SMKN 1 Palasah tends to apply simple and situational adjustments, while SMPN 2 Dawuan implements a more systematic process including assessment, situation analysis, strategy formulation, implementation, and monitoring. The impact at SMKN 1 Palasah is limited to improving student independence, while SMPN 2 Dawuan shows broader impacts on academic and social development as well as the creation of a more inclusive school culture. The conclusion emphasizes that well-planned strategies, facilities, teacher competence, and collaboration with parents and stakeholders are key to inclusive education success. Schools are recommended to develop clearer strategies, establish special inclusion teams, provide teacher training, and conduct regular evaluations to ensure effective and sustainable inclusive practices. Keywords: Strategic Management, Inclusive Education, Public Schools.